2021
DOI: 10.3389/fvets.2021.646247
|View full text |Cite
|
Sign up to set email alerts
|

GPGMH, a New Fixed Timed-AI Synchronization Regimen for Swamp and River Crossbred Buffaloes (Bubalus bubalis)

Abstract: The crossbreeding of Swamp and River type buffalo breeds is practiced for the improvement of milk yield and reproductive performance in swamp buffalo herds. This study aimed to modify the Ovsynch synchronization protocol (GPG) and improve the fixed-timed artificial insemination (FTAI) for better reproductive performance of crossbred buffaloes. Comparison of four conventional synchronization protocols [pregnant mare gonadotropin-prostaglandin F2α-gonadotropin-releasing hormone (PmPG), gonadotropin-releasing hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…The hypothesis of the present experiment was based on a preliminary study conducted [ 24 ] using crossbred buffaloes which reported improved reproductive parameters when hCG and mifepristone were included in the conventional OVS protocol. In the present study, nulli- and multiparous buffaloes were synchronized by the GPGMH and OVS protocol during different seasons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The hypothesis of the present experiment was based on a preliminary study conducted [ 24 ] using crossbred buffaloes which reported improved reproductive parameters when hCG and mifepristone were included in the conventional OVS protocol. In the present study, nulli- and multiparous buffaloes were synchronized by the GPGMH and OVS protocol during different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CL formed after hCG use has a similar steroidogenic activity on the progesterone hormone [ 26 ]. Additionally, its usage increases the functional CL area for the optimum progesterone level [ 24 ]. Also, the low response of heifers to GPGMH or OVS compared to multiparous buffaloes could be the result of the use of an inappropriate body weight of buffalo heifers or stress occurring during rigorous rectal palpation for ovarian dynamics, which led to low follicular output.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations